Bioactive glass air‐abrasion promotes healing around contaminated implant surfaces surrounded by circumferential bone defects: An experimental study in the rat. (5th January 2023) - Abushahba, Faleh; Areid, Nagat; Gürsoy, Mervi; Willberg, Jaana; Laine, Varpu; Yatkin, Emrah; Hupa, Leena; Närhi, Timo O.
Abstract: Objectives: The present study aimed to evaluate the healing of experimentally induced bone defects around contaminated dental implants after air‐abrasion using 45S5 or zinc oxide (ZnO)‐containing bioactive glasses (BAGs). Materials and Methods: One maxillary first molar was extracted from each Sprague–Dawley rat ( n = 30). After 4‐week healing, a titanium implant was placed in the extraction site with a circumferential bone defect. The rats were randomized into five different groups: (1) implants with Fusobacterium nucleatum and Porphyromonas gingivalis dual‐species biofilm (IB); (2) implants with biofilm subjected to inert glass air‐abrasion (inert); (3) sterile implants (S); (4) implants with biofilm subjected to 45S5 BAG air‐abrasion (45S5); and (5) implants with biofilm subjected to ZnO‐containing BAG air‐abrasion (Zn4). After 8‐week healing, maxillae were dissected, and histomorphometric analyses were performed. Results: The first bone‐to‐implant contact was significantly shorter for the inert (1.58 ± 1.16 mm; p = 0.016), S (0.28 ± 0.13 mm; p < 0.001), 45S5 (0.41 ± 0.28 mm; p < 0.001), and Zn4 (0.26 ± 0.16 mm; p < 0.001) groups compared to IB group. Also, significantly more bone‐to‐implant contact was seen for S (72.35% ± 8.32%; p < 0.001), 45S5 (57.91% ± 24.10%; p = 0.002), and Zn4 (70.49% ± 12.74%; p < 0.001) groups than the IB group. The bone volume with the threads demonstrated significantly higher value for S (69.32% ± 9.15%; p < 0.001), 45S5 (58.93% ± 23.53%; p = 0.001), and Zn4 (68.65% ± 12.41%; p < 0.001) groups compared to the IB group. The bone volume within the defects was significantly higher for S (68.79% ± 11.77%; p < 0.001), 45S5 (62.51% ± 20.51%; p = 0.002), and Zn4 (73.81% ± 15.07%; p < 0.001) groups compared to the IB group. Conclusions: This study suggests that air‐abrasion of contaminated moderately rough implant surfaces with either 45S5 or ZnO‐containing BAGs enhances osseointegration and bone defect regeneration.